STRATEGI ADAPTASI MGT RADIO 101.1 FM DALAM MEMPERTAHANKAN EKSISTENSI DI ERA DIGITAL - Jabbar, Ridwan Abdul; Sumadiria, Haris; Aziz Maarif, Abdul (Annaba: Jurnal Ilmu Jurnalistik, 2022)
This study aims to describe how MGT Radio 101.1 FM's strategy is to maintain its existence in the digital era. Researchers use the concept of strategic management from Fred R David who explains that in the strategy there are three stages, namely planning, implementation and evaluation. This research method uses a qualitative descriptive method. The results of the research show, (1) in the pre-production stage, the program director and producer are responsible for determining program planning, content ideas and script writing; (2) at the stage of production or implementation of the production of the MGT Radio program carried out by broadcasters through three stages, namely pre-on air, on air and closing; (3) the post-production stage, namely the final stage of the pre-production and production results as well as the evaluation carried out by MGT Radio in 3 periods, namely daily, weekly and monthly. At this stage the entire team including the board of directors is involved.